Lesser Tuberosity Avulsion Fracture in an 11-Year-Old Baseball Player due to Batting. (16th November 2021) - Cheng, Ryan; Moran, Jay; Smith, Samantha; Li, Don; Schneble, Christopher A.; Chan, Shin Mei; Gardner, Elizabeth C.
Abstract : Case . We report an 11-year-old male who sustained a lesser tuberosity avulsion fracture of the proximal humerus upon making contact with a baseball during an at-bat. This injury was neglected for 14 months and was eventually detected by an axillary radiograph and subsequent MRI. He successfully underwent an open surgical repair and regained full range of motion and level of activity at 1-year follow-up. Conclusion . In pediatric baseball players, lesser tuberosity avulsion fractures may occur upon striking a baseball with a bat. Even after being neglected for several months, these injuries can be treated successfully with an open surgical repair.